The Royal Ballet 161 Images Review - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review of Johan Persson's 161 Images. PALABRAS CLAVE: Johan Persson, photograps.
The Royal Ballet 161 Images. Johan Persson, Oberon Books, 2003.